Romanian media and public's safety during information warfare - Ungur-Brehoi, Carmen (International Journal of Legal and Social Order, 2023)
Nowadays, wars are no longer fought exclusively on the front, but often, even more effectively, behind the front line, in a hybrid way, in the information environment. The Romanian mass media, like the international media, is recently more and more frequently assaulted by examples of disinformation, propaganda, cybernetic attacks. Is there information security for the Romanian reader during the international war? How sure is the reader that the data he has read is correct, credible, or truthful information? We will try to see the answer reflected in the case study regarding the media in current Romania, comparing a national newspaper, Adevarul, and a local one, Jurnal bihorean, on the use and definition of the chimera-phrase “hybrid war”.